TOP MANAGEMENT TEAM AGREEMENT ABOUT THE STRATEGIC DECISION PROCESS: A TEST OF SOME OF ITS DETERMINANTS AND CONSEQUENCES - IAQUINTO, ANTHONY L.; FREDRICKSON, JAMES W. (Strategic Management Journal, 1997)
The level of agreement among a firm’s top executives about how things are done in that firm has a variety of important implications. For example, agreement about a firm’s decision-making norms may allow members of the top management team (TMT) to focus on the substance of their most critical decisions and not get bogged down in debates about the process. In the present study, data from 65 firms in two industries were used to identify determinants and consequences of TMT agreement about the comprehensiveness of the strategic decision process. Results for consequences indicate that the level of TMT agreement was positively related to organizational performance. As for the determinants of agreement, organizational size was negatively related to agreement but past performance exhibited no association. Therefore, the results suggest that it is TMT agreement that influences performance, not the reverse. In addition, a surprising result was that firms in an industry with an unstable environment exhibited significantly more agreement about the process than did their counterparts in an industry whose environment was stable. © 1997 by John Wiley & Sons, Ltd.